2020
DOI: 10.1186/s12885-020-07373-4
|View full text |Cite
|
Sign up to set email alerts
|

5α-reductase inhibitors impact prognosis of urothelial carcinoma

Abstract: Background 5α-reductase inhibitors (5-ARIs) inhibit the pathway of converting the testosterone to dihydrotestosterone and are widely used in benign prostatic hyperplasia patients. Since androgen receptor activation may play a role in urothelial tumorigenesis, we conducted this retrospective cohort study to determine whether 5α-reductase inhibitors (5-ARIs) administration is associated with bladder cancer mortality, bladder cancer recurrence and upper tract urothelial carcinoma mortality, using the Taiwan Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Further assessment of eligibility, based on the study of the full-text papers, led to the exclusion of 44 papers. Finally, 14 studies (6 preclinical and 8 clinical) were included in the final analysis ( Figure 1 ) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Of these, 6 studies were included in the quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Further assessment of eligibility, based on the study of the full-text papers, led to the exclusion of 44 papers. Finally, 14 studies (6 preclinical and 8 clinical) were included in the final analysis ( Figure 1 ) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Of these, 6 studies were included in the quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, eight retrospective case-control studies were identified involving a total of 17,454 male patients [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The study characteristics, patients’ demographics and tumour features are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations